Antiphospholipid antibodies and hyperhomocysteinaemia in patients with vascular occlusive disease - Casais, Patricia (2006)
Hyperhomocysteinemia (HHcy), lupus anticoagulant (LA) and anticardiolipin antibodies (ACA) are independent risk factors for thrombosis. Even though risks are cumulative, the clinical impact of the association is unknown. Preliminary data suggested that HHcy might be associated with transient LA and ACA, disappearing after lowering HHcy. We prospectively evaluated the association of HHcy and LA/ACA, the effect of lowering HHcy with folic acid in LA behavior, and the correlation of the initial dRVVT with LA behavior after folic acid in 210 patients with thrombosis and adverse pregnancy outcomes. Prevalence of HHcy among patients with LA/ACA was 40%. Thirty-one patients exhibited only HHcy (15%; Group 1), 106 (50%; Group 2) had only LA/ACA, while 73 (35%; Group 3) had both. After therapy, 63% and 64% of LA/ACA remained positive in Group 3 and 2, respectively. We observed a trend towards a more positive dRVVT in persistent LA after lowering HHcy. No differences in clinical presentation or in outcomes after two years of follow-up were observed among the groups. Even though the association of HHcy and LA/ACA is common in patients with thrombosis, it might have no prognostic implications if Hcy levels are lowered. Currently, no laboratory findings correlate with LA behavior, which is independent of homocysteine levels and vitamin treatment. © 2006 Schattauer GmbH, Stuttgart.